Smiths-Magenis Syndrome: A Therapeutic Challenge - Pedreira, Beatriz; Aveiro, Ana Cristina (Gazeta Médica, 2025)
Smith-Magenis syndrome is a rare disease characterized by developmental delay, behavioral changes and sleep problems secondary to circadian rhythm deregulation of melatonin. With growth there is a progressive worsening of sleep problems and violent behaviors. This is a case of a child with Smith-Magenis syndrome with severe behavioral and sleeping problems in which the association of a ?-blocker during the day with melatonin of prolonged release at night achieved a satisfactory control of symptomatology. Although the literature available suggests acebutolol (?-1 selective blocker), propranolol (?-blocker non-selective) was used given the broad availability and vast experience of use in Portugal. The scientific literature available on pharmacological approaches in Smith-Magenis syndrome is scarce even regarding the prescription of ?-blockers. No article could be found concerning propranolol use in the particular case of this syndrome.